Penggunaan Media Sosial Sebagai Media Komunikasi Dan Promosi Nee Studio Pada Gen Z - Ramania, Made Indira Allodya (Jurnal VICIDI, 2024)
The lack of spaces for content creation and creative activities in Surabaya is still a significant concern for Gen Z individuals and influencers in Surabaya. Several new creative studio businesses in Surabaya need to put more effort into promoting their businesses to reach the active target market using social media. To succeed in targeting Gen Z and influencers, it is essential to implement social media promotion strategies to enhance brand awareness. Staying up-to-date with current social media trends and studying literature on marketing strategies, communication, and the habits of Gen Z in using social media are crucial. According to literature reviews, it can be said that consistent, engaging, and interactive social media content is highly effective in building good customer engagement between the brand and customers on social media. By utilizing social media optimally and appropriately, it is expected that the brand's message will be directed towards the target market, leading to an increased brand awareness for creative studio businesses.